Intellectual property rights in agricultural biotechnology - Erbisch, Frederic H.; Maredia, Karim M. (Biotechnology in agriculture series, 2004)
During the past twenty-five years, biotechnology has revolutionized agricultural research. The enormous potential, together with a landmark decision by the US Supreme Court to allow the patenting of genetically-engineered organisms has encouraged private sector companies to invest in agricultural biotechnology research programmes. This has contributed to a rapid growth in interest in intellectual property rights as applied to this subject. The first edition of this book was published in 1998. Now fully revised and updated it presents definitive information on intellectual property law in a simp.